A RARE ENCOUNTER: UNVEILING THE CLINICAL SPECTRUM OF SUBACUTE THYROIDITIS - Panerselvam, Nalini; Gopal, Nishkkriyaa; Veerappan, Ashok; Wong, Lee Theng; Sun, Choon Peng (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Subacute thyroiditis (SAT) is a rare, self-limiting inflammatory thyroid disease. It usually presents with neck pain, transient thyrotoxicosis and systemic dysfunction. It predominantly affects women aged 20–50 years and is commonly associated with viral infections or autoimmune responses. We report an unusual case of SAT with atypical presentation, highlighting its diagnostic challenges and management. CASE A 38-year-old female presented with fever and painless anterior neck swelling with significant weight loss of 9 kg for two weeks, preceded by left otalgia for one week. She denied any significant past medical history, was not taking any medications and reported no family history of thyroid diseases. On examination, the patient was calm, and except for a high-grade fever, there were no other signs of sepsis. She had a palpable, non-tender, diffuse goiter without thyroid eye signs or fine tremors. Laboratory investigations showed low thyroid-stimulating hormone (TSH) at 0.05 mIU/L, with elevated free T4 (51.6 pmol/L) and free T3 (14.1 pmol/L), yielding a T3/T4 ratio of <0.3. C-reactive protein (CRP) was markedly elevated at 162 mg/L, though white cell count remained normal. Anti-thyroid antibodies were negative. Thyroid ultrasound revealed a multinodular goiter (TIRADS 3), while thyroid scintigraphy demonstrated low uptake, confirming SAT. These findings indicated the hyperthyroid phase of SAT. Based on clinical symptoms, laboratory results, and imaging findings, a diagnosis of subacute thyroiditis was made. The patient was treated with corticosteroids to reduce inflammation alongside symptomatic treatment. The patient responded well, with resolution of symptoms within four weeks. Follow-up thyroid function tests normalized after two months, with no recurrence of symptoms or persistence of hyper/hypothyroidism was noted. CONCLUSION This case emphasizes that SAT should be considered in patients presenting with fever and elevated free T4 who lack typical thyrotoxic features, especially following a recent infection. The painless goiter and significantly elevated free T4 in this case represented atypical features that could have easily led to misdiagnosis.